Satellite Tracking of Post-nesting Green Sea Turtles (Chelonia mydas) From Ras Baridi, Red Sea - Al-Mansi, Ahmed M.; Sambas, Anas Z.; Abukaboos, Baleegh A.; Al Zahrani, Ahmed H.; Abdulaziz, Ahmed S.; Almasabi, Ali A.; Alkreda, Raed S.; Miller, Jeff (Frontiers in Marine Science, 2021)
Identifying migratory pathways and linking nesting sites to foraging areas is essential for effective conservation management of migratory species, such as marine turtles. Post-nesting marine turtles disperse from their nesting sites to multiple foraging areas located from a few to hundreds of kilometers away. Over a six-year period 16 female green turtles (Chelonia mydas) were equipped with satellite transmitters between October and December of five nesting seasons to determine their migratory routes from their nesting area at five contiguous beaches at Ras Baridi, Saudi Arabia, to their foraging areas. All foraging areas for these turtles were located in shallow coastal areas or in shallow areas around offshore islands within the Red Sea basin. The majority (n = 12) migrated through the shallow (<200 m) water along the coastal margin to reach foraging areas located to the North (n = 4) and South (n = 12) of the nesting site. Four turtles crossed the deep trough of the Red Sea during their journeys. Ten of the 16 turtles migrated to foraging areas within the territorial waters of Saudi Arabia. The other six turtles migrated to foraging areas in Egypt (n = 4) and Eritrea (n = 2). These 16 turtles traveled between 130 and 1749 km from their nesting site to foraging areas located in the northern, middle and southern parts of the Red Sea. Because these turtles utilized foraging areas in at least three countries (Saudi Arabia, Egypt, and Eritrea) and one passed through the territorial waters of Sudan, conservation and management of green turtles in the Red Sea requires multinational cooperation to address anthropogenic threats in the region.